Fluoride toothpaste, sanitary surveillance and the SUS: the case of Manaus-AM, Brazil - Mayara Costa Carneiro Ramos; Maria Augusta Bessa Rebelo; Janete Maria Rebelo Vieira; Luís Fernando Bandeira Miranda; Cinthia Pereira Machado Tabchoury; Jaime Aparecido Cury (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To determine the anticaries potential of toothpastes distributed by the primary health care public clinics (UBS) of Manaus, AM. METHODS Ninety-nine tubes of toothpaste from four commercial brands were collected from October 7, 2019 to October 11, 2019 in 16 UBS. They were assigned a code by brand and source UBS. According to the information on the packaging, the four brands and their batches were formulated with sodium monofluorophosphate (Na2FPO3) and most (91%) had calcium carbonate (CaCO3) as an abrasive. We determined the concentrations of total fluoride (TF = TSF + InsF) and total soluble fluoride (TSF = F ions- or FPO32-), to certify whether they were in compliance with resolution ANVISA RDC No. 530 (maximum of 1,500 ppm TF) and whether they had anticaries potential (minimum of 1,000 ppm TSF). The analyses were performed with a ion- specific electrode. RESULTS The concentrations (ppm F) of TF [mean; standard deviation (SD); n] found in toothpaste brands A (1,502.3; SD = 45.6; n = 33), B (1,135.5; SD = 52.7; n = 48) and D (936.8; SD = 20.5; N = 8) were close to those stated on the package, 1,500, 1,100 and 1,000 ppm F, respectively. In toothpaste C, we found a mean of 274.1 ppm (SD = 219.7; n = 10) of TF, which diverges from the declared concentration of 1,500 ppm F. In addition, the five tubes of lot no. 11681118 of toothpaste C did not contain fluoride. Regarding TSF, with the exception of toothpaste D (937.9; SD = 40.29), the others had a lower concentration than their respective TF. CONCLUSION We found serious problems of quantity and quality of fluoride in toothpaste distributed by the SUS in Manaus, which shows the need for surveillance of these products and confirms the urgency of revising resolution RDC No. 530.